Interpreting Symbols and Metaphors in Short Stories of Shashi Deshpande ('Why A Robin', 'It was Nightigale', 'It was Dark' ) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
Symbols hold the key to unlocking the depths of the subconscious of reader's mind. They resonate the themes and characters of a story.In literature, authors often use, symbols (as symbolism) to give their work with more meaning and to make a story be about more than events it deseribes. The use of any person, situation or object to represent an idea of some sort is called symbolism. It refers to the use of represent tational imagery. The writer employs an image with a deeper. non-literal meaning for the purpose of conveying complex ideas. Usually a physical object or phenomenon is used by the writers as symbols. Characters and events can also be symbolic. Symbolim is very common in all sorts of narrative be it poetry, prose or fiction.Writers use symbols to convey ideas, without actually specifying the idea in order to get the reader to contemplate a theme that spans time and its relevence to culture and society. Metaphors help the writer to develop the symbolic meaning of their text. A metaphor is kind of like a symbol, but it is usually used briefly, whereas a symbol is usually extented throught a story.Shashi Deshpande has used various symbols and metaphors in her short fiction ranging from natural objects to characters and a specific phenomenon.